2011
DOI: 10.1200/jco.2010.32.4079
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Breast Cancer in Women With and Without a History of Radiation for Hodgkin's Lymphoma: A Multi-Institutional, Matched Cohort Study

Abstract: In women with a history of RT for HL, breast cancer is diagnosed at an earlier stage, but these women are at greater risk for bilateral disease and are more likely to die as a result of causes other than breast cancer. Our findings support close follow-up for contralateral tumors in these patients and ongoing primary care to manage comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 41 publications
10
65
1
Order By: Relevance
“…Some studies have assessed if BC following HL differs from primary BC in terms of tumor characteristics [16 -19] or prognosis [8,[17][18][19][20][21][22]. In particular, a large population-based study using the dataset from the Surveillance, Epidemiology and End Results (SEER) program reported that, among women with localized BC, patients with previous HL had a twofold greater risk for death resulting from BC than patients without previous HL [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have assessed if BC following HL differs from primary BC in terms of tumor characteristics [16 -19] or prognosis [8,[17][18][19][20][21][22]. In particular, a large population-based study using the dataset from the Surveillance, Epidemiology and End Results (SEER) program reported that, among women with localized BC, patients with previous HL had a twofold greater risk for death resulting from BC than patients without previous HL [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this group, mammography and magnetic resonance imaging complement each other in breast cancer screening. 31 Ng et al reported that, among these patients, the sensitivity of mammography and magnetic resonance imaging, when used separately, is 68% and 67%, respectively. However, when the two methods are used in combination, the sensitivity increases to 94%.…”
Section: Chest Wall Irradiationmentioning
confidence: 99%
“…8,9 Late effects, especially SPM and cardiovascular events, are well-known after first-line treatment of HL. [10][11][12][13][14][15][16] In contrast, only a few retrospective studies have addressed long-term effects after ASCT for relapsed or refractory HL. 17,18 Thus, long-term prospective data are lacking for first-relapsed or refractory HL treated with ASCT.…”
Section: A B D Cmentioning
confidence: 99%